Features of distribution and causes of risk-oriented behavior among young people (by the example of psychoactive substances use) - Kukovska, I. L.; Ivanushko, Ya. G.; Romaniv, L. V.; Pylyp, G. N.; Pishak, O. V.; Logush, L. G. (Journal of Education, Health and Sport, 2017)
The aim of the present study was to investigate the university students’ views of possible situations and the reasons for the use of substances that can be addictive by their peers. So-called psychoactive substances (tobacco, alcohol, drugs, energy drinks) can act as risk factors and contribute to the development of a number of socially significant diseases. The study did not provide for the study of the spread of harmful habits among young people, but only an analysis of the responses concerning the situation and the reasons for these phenomena. The study involved 137 students aged 17 to 21 years. It was found that the majority of respondents can not identify a single best reason, but pointed out a few of these reasons and situations. It is shown that in the opinion of young people, the freer use of psychoactive substances among young people is primarily promoted by visits to discos, meeting with friends who are on the background of the lack of interesting activities and hobbies, as well as the situation, accompanied by an insufficient level of adult supervision, including the holidays period. Analysis of the study results suggests a lack of skill level output from "uncomfortable" psychological situations among young people. The survey results indicate key influence of family and social environment on the degree of the risk-oriented behavior manifestation of young people. Taking into account the significant contribution of risk factors in the state of public health indicators, analysis of the processes of formation and perception of health risks among young people requires special attention. Conducting further systematic sociological studies, which will condition the direction and influence the quality of health preservation programs seems relevant and appropriate.